Upaya Kepolisian Negara Republik Indonesia dalam Mencegah Tindak Pidana Korupsi - Michael Pedrin (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2024)
Corruption is one of the most destructive social, political and economic problems in various countries. Corruption is also a serious problem faced by all countries in the world, and Indonesia is one of them. Corruption is not only an act that violates the law, but also violates moral values, destroys trust, and hinders domestic progress. Efforts to eradicate corruption in Indonesia have been carried out in various ways, but until now corruption still occurs in various ways and is carried out by different political parties and institutions. Corruption poses several dangers, including threats to society, individuals, the younger generation, politics and the country's economy. In Law Number 31 of 1999, criminal acts of corruption are classified into the following categories: financial damage, bribery, embezzlement from public office, extortion, fraud, procurement disputes, gratification. Eradicating corruption requires integrated law enforcement, international cooperation and harmonious regulations. Not only international cooperation, but increasing effectiveness in preventing corruption, community involvement is needed. Public participation in supervision and stricter law enforcement can create an anti-corruption system. By involving the community we can strengthen transparency and minimize acts of corruption